Transcranial 3D ultrasound localization microscopy using a large element matrix array with a multi-lens diffracting layer: an in vitro study. (7th April 2023) - Favre, Hugues; Pernot, Mathieu; Tanter, Mickael; Papadacci, Clément
Abstract: Objective . Early diagnosis and acute knowledge of cerebral disease require to map the microflows of the whole brain. Recently, ultrasound localization microscopy (ULM) was applied to map and quantify blood microflows in 2D in the brain of adult patients down to the micron scale. Whole brain 3D clinical ULM remains challenging due to the transcranial energy loss which reduces significantly the imaging sensitivity. Approach . Large aperture probes with a large surface can increase both the field of view and sensitivity. However, a large active surface implies thousands of acoustic elements, which limits clinical translation. In a previous simulation study, we developed a new probe concept combining a limited number of elements and a large aperture. It is based on large elements, to increase sensitivity, and a multi-lens diffracting layer to improve the focusing quality. In this study, a 16 elements prototype, driven at 1 MHz frequency, was made and in vitro experiments were performed to validate the imaging capabilities of this new probe concept. Main results . First, pressure fields emitted from a large single transducer element without and with diverging lens were compared. Low directivity was measured for the large element with the diverging lens while maintaining high transmit pressure. The focusing quality of 4 × 3cm matrix arrays of 16 elements without/with lenses were compared. In vitro experiments in a water tank and through a human skull were achieved to localize and track microbubbles in tubes. Significance. ULM was achieved demonstrating the strong potential of multi-lens diffracting layer to enable microcirculation assessment over a large field of view through the bones.